Callus Induction and its Comparative Biochemical Studies from Seeds of Nigella Sativa Linn. - Meena, Mukesh kumar (International Journal of Pharmaceutical & Biological Archive, 2017)
Nigella sativa L. is a medicinal spice plant belonging to the family Ranunculaceae. It is an annual flowering herb and widely used medicinal plant throughout the world. Nigella sativa has several therapeutic effects which are attributed to its constituents like nigellicine, nigellidine, thymoquinone, dithymoquinone, thymol and carvacrol. Several beneficial pharmacological properties of this plant such as anti-oxidant, anti-bacterial, anti-histaminic, antihypertensive, hypoglycemic, anti-fungal, antiinflammatory, anti-cancer and immunomodulatory effects were reported. The seeds of this plant have various health benefits in treating Diabetes, epilepsy, cancer, heart attack/damage, leukemia, etc. Thus, in vitro callus induction with different concentrations of growth regulators viz NAA, IAA, 2,4-D has been optimized and callus production was maximum at 2,4-D (3.0 mg/l). The highest total level of primary metabolites was found in callus culture of Nigella sativa as compared to the seeds of plant. Thus, the present study is an effort to raise in vitro callus and its comparative biochemical investigation with seeds for further pharmacological advantages.